An RFID-based variable rate technology fertilizer applicator for tree crops - Ishola, Tajudeen Abiodun; Yahya, Azmi; Mohammed Shariff, Abdul Rashid; Abd Aziz, Samsuzana (Asian Network for Scientific Information, 2013)
Variable Rate Technology (VRT) fertilizer application could reduce pollution through leaching and volatilisation. A VRT fertilizer applicator for band application of granular fertilizer on tree crop was designed, developed and tested. The applicator was equipped with a long-range Radio Frequency Identification (RFID) reader to detect the stored tag ID on the available passive RFID tags attached on the trees. When the control program received the RFID tag ID on the tree, it related the tag ID to the information in a database and triggered the VRT fertilizer applicator system to apply precise amount of fertilizer to that particular area. Based on the experimental evaluation of the response time of the VRT applicator, it was found to take 2-3 sec to changes in application rate depending on the magnitude of the change. The VRT applicator has a field capacity of 7.22 and 7.71 ha h-1 with field efficiencies of 0.54 and 0.52 at the travelling speed of 4.43 and 4.92 km h-1, respectively. The use of RFID technology has proven to be able to serve as alternative solution for geo-location determinations for the fertilizer applicator in the plantations where the presence of tree canopies has hindered the use of GPS technology.